-(2a-2)+3=3-(2a+5)

Simple and best practice solution for -(2a-2)+3=3-(2a+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(2a-2)+3=3-(2a+5) equation:


Simplifying
-1(2a + -2) + 3 = 3 + -1(2a + 5)

Reorder the terms:
-1(-2 + 2a) + 3 = 3 + -1(2a + 5)
(-2 * -1 + 2a * -1) + 3 = 3 + -1(2a + 5)
(2 + -2a) + 3 = 3 + -1(2a + 5)

Reorder the terms:
2 + 3 + -2a = 3 + -1(2a + 5)

Combine like terms: 2 + 3 = 5
5 + -2a = 3 + -1(2a + 5)

Reorder the terms:
5 + -2a = 3 + -1(5 + 2a)
5 + -2a = 3 + (5 * -1 + 2a * -1)
5 + -2a = 3 + (-5 + -2a)

Combine like terms: 3 + -5 = -2
5 + -2a = -2 + -2a

Add '2a' to each side of the equation.
5 + -2a + 2a = -2 + -2a + 2a

Combine like terms: -2a + 2a = 0
5 + 0 = -2 + -2a + 2a
5 = -2 + -2a + 2a

Combine like terms: -2a + 2a = 0
5 = -2 + 0
5 = -2

Solving
5 = -2

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 6(3-2)x=54 | | 5(a+4)-(4a+4)=4(5a-2)+5 | | 900=x-.5 | | 7(2y+7)+(-36y)= | | 6x^5-4x^2+10x=0 | | -6n-1n=16 | | x^8-2x=0 | | 8(-16)/2(-8)-5(-3) | | 4-4(2a-3)=0 | | 6-3|-8r-9|=-15 | | (2x-1)/(9-x^2) | | -3|9m+2|+10=10 | | y^1/6(y^11/6+y^23/6) | | log(x+1)+2*log(x)=log(x^2+8) | | 4-9|-6-b|=-14 | | 10-10|-8k+4|=40 | | 17/x+7 | | 7.6=p-6 | | -8|3-8k|=40 | | Ln(3x)+5=7 | | 2/7x14/3 | | 3|x/9|+7=8 | | 5(3x-2)-8(2x+3)-9=51 | | -2(2x+2)=4(2-x)-12 | | 2x^2+3=y | | 61-4x=10+19 | | m/-4=-2.27 | | -5(4a-5)=2(3-10a)+19 | | -52-5x=8-8x | | 31x-13=42 | | 2(3x+1)+5(3x+1)= | | 9[v+2]-3v=2(3v+3)-11 |

Equations solver categories